Cold Abscess of the Thigh in an Infant - Mishra, D; Mohta, A; Arora, P (Kathmandu University Medical Journal, 2014)
Local and minor adverse reactions to diphtheria–pertussis–tetanus (DPT) vaccination are usually mild and appear within 48 hours of vaccination. We herein report a rare association with intramuscular DPT injection and discuss pertinent issues. Primary tuberculous abscess was the final diagnosis. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11035 Kathmandu University Medical Journal Vol.11(1) 2013: 86-87